Isolation and Characterization of Starch from Horse Gram - B.G.Shinde2, U.D.Chavan*1; Kadam3, S.S. (Global Journal of Food and Agribusiness Management, 2011)
Starch was extracted from white, red and black cultivars of horse gram using cold water, hot water and dilutes alkali. A hot water extracted maximum of 28.4 %, 31.1 % and 29.0 % starch from seeds of white, red and black cultivars. The isolated starch was characterized by proximate composition contents of amylose, swelling factor, amylose leaching and susceptibility to enzyme/acid hydrolysis.